Resin composition for film formation, overlaminate film, and license plate

The film forming resin composition, comprising a polyurethane resin, isocyanate-based crosslinking agent, and crosslinking catalyst, addresses the challenge of achieving both solvent resistance and low-temperature impact resistance in films, making them suitable for use in cold regions and harsh environments.

JP2025070318AActive Publication Date: 2025-05-02NIPPON CARBIDE KOGYO KK
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2023180541
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-05-02
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

Existing films used for protecting design layers on outdoor signs, motorcycles, and four-wheeled vehicles face challenges in achieving both solvent resistance and low-temperature impact resistance, particularly in cold regions.

Method used

A film forming resin composition comprising a polyurethane resin, an isocyanate-based crosslinking agent, and a crosslinking catalyst, with specific ratios and properties, is used to form a film with excellent solvent resistance and low-temperature impact resistance.

Benefits of technology

The film forming resin composition effectively enhances the solvent resistance and low-temperature impact resistance of the films, making them suitable for use in cold regions and harsh environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070318000002
    Figure 2025070318000002
  • Figure 2025070318000003
    Figure 2025070318000003
  • Figure 2025070318000004
    Figure 2025070318000004
Patent Text Reader

Abstract

To provide a resin composition for film formation that is capable of forming a film exhibiting excellent solvent resistance and low-temperature shock resistance.SOLUTION: The present invention provides a resin composition for film formation, comprising: a polyurethane resin, an isocyanate-based crosslinking agent, and a crosslinking catalyst, wherein based on 100 pts.mass of the polyurethane resin, the content of the isocyanate-based crosslinking agent is 10 to 30 pts.mass and the content of the crosslinking catalyst is 0.01 pt.mass or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a film-forming resin composition, an overlaminate film, and a license plate. [Background technology]

[0002] Films with a design layer formed by printing or other methods are used to decorate outdoor signs and two-wheeled and four-wheeled vehicles. To protect the design layer, a transparent film is used as a surface protective layer. Films made primarily from polyvinyl chloride resin, fluororesin, acrylic resin, or urethane resin are often used to protect the design layer. Patent Document 1 discloses an exterior metallic film provided with a surface resin layer made of a polyvinyl chloride resin. Patent Document 2 discloses a laminate sheet for automobile decoration, which is made of vinylidene fluoride resin and acrylic resin and has a surface protective layer with a vinylidene fluoride resin content of 50% by weight or more. Patent Document 3 discloses a colored acrylic resin film used as a surface material for retroreflective sheeting. Patent Document 4 discloses a sheet-like laminate applicable to interior and exterior materials for automobiles and the like, which is formed by laminating a polyurethane layer onto a thermoplastic resin sheet. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 2-004506 [Patent Document 2] JP 2001-071428 A [Patent Document 3] JP 2006-282902 A [Patent Document 4] JP 2008-023854 A Summary of the Invention [Problem to be solved by the invention]

[0004] Patent Document 1 describes that the surface resin layer made of a polyvinyl chloride resin has excellent solvent resistance (gasoline resistance), but makes no mention of low-temperature impact resistance. Patent Document 2 describes that the surface protective layer made of vinylidene fluoride resin and acrylic resin has excellent chemical resistance (gasoline resistance), but makes no mention of low-temperature impact resistance. Although Patent Document 3 describes that the colored acrylic resin film is excellent in weather resistance and the like, it is silent about chemical resistance and low-temperature impact resistance. Patent Document 4 describes that a sheet-like laminate having good weather resistance can be obtained by using a specific polycarbonate polyol as a component constituting a polycarbonate-based water-based polyurethane, but does not describe solvent resistance or low-temperature impact resistance.

[0005] Furthermore, according to the findings of the present inventors, films using polyvinyl chloride resin or fluororesin are brittle at low temperatures, and there is concern that they may crack due to impact when used outdoors in cold regions. In addition, films using acrylic resins do not have the solvent resistance required for use in two-wheeled or four-wheeled vehicles, and cannot be used.In addition, they have poor impact resistance at low temperatures, raising concerns about their use in cold regions. In addition, a film using a urethane resin can be given solvent resistance by chemically crosslinking reactive functional groups contained in the urethane resin, but the low-temperature impact resistance is deteriorated. On the other hand, a urethane resin that is not chemically crosslinked has good low-temperature impact resistance but poor solvent resistance. It is not necessarily easy to achieve both low-temperature impact resistance and solvent resistance by using a urethane resin. As described above, when a vinyl chloride resin, a fluororesin, an acrylic resin, a urethane resin, or the like is used for the surface protective layer, it is sometimes difficult to achieve both solvent resistance and low-temperature impact resistance. The present disclosure has been made in consideration of the above-mentioned conventional circumstances, and aims to provide a film-forming resin composition capable of forming a film having excellent solvent resistance and low-temperature impact resistance, as well as an overlaminate film and a license plate using a surface protection film formed from this film-forming resin composition. [Means for solving the problem]

[0006] Specific means for achieving the above object are as follows. <1> The composition includes a polyurethane resin, an isocyanate crosslinking agent, and a crosslinking catalyst, A film-forming resin composition, wherein the content of the isocyanate-based crosslinking agent is 10 parts by mass to 30 parts by mass, and the content of the crosslinking catalyst is 0.01 parts by mass or more, relative to 100 parts by mass of the polyurethane-based resin. <2> The polyurethane resin includes at least one selected from the group consisting of polycarbonate-based polyurethane resins, polyester-based polyurethane resins, and polyether-based polyurethane resins. <1> The film-forming resin composition according to claim 1 . <3> The polyurethane resin has an acid value of 1.0 mgKOH / g or less, and a hydroxyl value of 30 mgKOH / g or less. <1> or <2> The film-forming resin composition according to claim 1 . <4> The crosslinking catalyst comprises a metal crosslinking catalyst. <1> ~ <3> 13. The film-forming resin composition according to claim 12 . <5> The metal cross-linking catalyst is at least one of tin 2-ethylhexanoate and di-n-octyltin dilaurate. <4> The film-forming resin composition according to claim 1 . <6> <1> ~ <5> 13. An overlaminate film comprising: a surface protective film formed from the film-forming resin composition according to any one of claims 1 to 12; and a pressure-sensitive adhesive layer provided on one side of the surface protective film. <7> The gel fraction of the surface protective film is 20% by mass to 60% by mass. <6> 2. The overlaminate film according to claim 1 . <8> A plate base material and a plate provided on one surface side of the plate base material. <6> or <7> A license plate comprising the overlaminate film described in claim 1. <9> An image receiving layer is provided between the plate substrate and the overlaminate film. <8> The license plate described in. Effect of the Invention

[0007] According to the present disclosure, it is possible to provide a film-forming resin composition capable of forming a film having excellent solvent resistance and low-temperature impact resistance, as well as an overlaminate film and a license plate using a surface protection film formed from this film-forming resin composition. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a cross-sectional view of one embodiment of the overlaminate film of the present disclosure. [Diagram 2] FIG. 1 is a cross-sectional view of one embodiment of the license plate of the present disclosure. [Diagram 3] FIG. 13 is a cross-sectional view of another embodiment of the license plate of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless specifically stated. The same applies to the numerical values ​​and their ranges, and do not limit the present disclosure. In the present disclosure, when an embodiment is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the size of the members in each drawing is conceptual, and the relative relationship of the size between the members is not limited thereto. In addition, in each drawing, the same reference numerals are given to members having substantially the same functions, and duplicated descriptions may be omitted.

[0010] In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple types of corresponding substances. When multiple types of substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, the terms "layer" and "film" include cases where the layer or film is formed over the entire area when the area in which the layer or film is present is observed, as well as cases where the layer or film is formed over only a portion of the area. In this disclosure, the term "lamination" refers to stacking layers, where two or more layers may be bonded together or where two or more layers may be removable. In the present disclosure, "(meth)acrylic" means at least one of acrylic and methacrylic. In the present disclosure, the average thickness of a layer or film is a value calculated as the arithmetic mean value of thicknesses measured at five points on a target layer or film. The thickness of the layer or film is the value measured using a constant pressure thickness gauge (measuring probe diameter 5 mm). In the present disclosure, the term "solid content" refers to components other than the solvent contained in the composition. In this disclosure, "solvent" means water and / or an organic solvent.

[0011] <Film-forming resin composition> The film-forming resin composition of the present disclosure comprises a polyurethane resin, an isocyanate crosslinking agent, and a crosslinking catalyst, and the content of the isocyanate crosslinking agent is 10 parts by mass to 30 parts by mass, and the content of the crosslinking catalyst is 0.01 parts by mass or more, relative to 100 parts by mass of the polyurethane resin. According to the film-forming resin composition of the present disclosure, it is possible to form a film having excellent solvent resistance and low-temperature impact resistance. The reason for this is not clear, but is presumed to be as follows. It is believed that the film-forming resin composition of the present disclosure contains a polyurethane resin, an isocyanate crosslinking agent, and a crosslinking catalyst, and thus a number of reactions occur as described below. First, it is believed that the urethane bond in the polyurethane resin and the isocyanate group in the isocyanate crosslinking agent form an allophanate bond, which creates a branched structure in the polyurethane resin. Secondly, it is thought that unreacted isocyanate-based crosslinking agent that has not reacted with the polyurethane resin may form polymers through reaction between other isocyanate-based crosslinking agents, or that the isocyanate groups may react with water in the environment to form urea. Thirdly, it is believed that a pseudo-IPN structure (physical crosslinking) is formed by entanglement of the branched polyurethane resin produced in the first reaction and the isocyanate polymers and urea produced in the second reaction. In addition to the formation of chemical crosslinks such as in the first and second reactions described above, physical crosslinks such as in the third reaction occur, resulting in high cohesive strength in the areas where the polyurethane resin, isocyanate polymer, and urea are entangled, and high flexibility of the polyurethane resin in the areas where they are not entangled. From the above, it is presumed that the film-forming resin composition of the present disclosure makes it possible to form a film that has excellent solvent resistance and low-temperature impact resistance.

[0012] Each component constituting the film-forming resin composition of the present disclosure will be described in detail below. The film-forming resin composition of the present disclosure includes a polyurethane resin, an isocyanate crosslinking agent, and a crosslinking catalyst, and may include other components such as a solvent, a plasticizer, a softener, a dye, a pigment, an inorganic filler, an ultraviolet absorber, a light stabilizer, an antioxidant, a defoaming agent, and a surfactant, as necessary.

[0013] (Polyurethane resin) The film-forming resin composition of the present disclosure includes a polyurethane resin. In the present disclosure, the term "polyurethane resin" refers to a resin obtained as a reaction product of a polyol, an organic polyisocyanate, and a chain extender used as needed. The type of polyurethane resin is not particularly limited, and conventionally known polyurethane resins such as polycarbonate-based polyurethane resins, polyester-based polyurethane resins, and polyether-based polyurethane resins can be used. The polyurethane resins may be used alone or in combination of two or more types. When the acid value and hydroxyl value of the polyurethane resin are low, the proportion of urethane bonds among the reactive groups in the polyurethane resin is relatively high, so that the urethane bonds and the isocyanate groups of the isocyanate crosslinking agent react to form allophanate bonds. When the acid value and hydroxyl value of the polyurethane resin are low, more of the isocyanate crosslinking agent remains unreacted with the polyurethane resin, so that isocyanate multimers and urea are easily formed. This makes it easier to form the pseudo-IPN structure described above, so that the solvent resistance and low-temperature impact resistance of the film formed from the film-forming resin composition of the present disclosure tend to be further improved. From this viewpoint, the polyurethane resin preferably has an acid value of 1.0 mgKOH / g or less and a hydroxyl value of 30 mgKOH / g or less, more preferably an acid value of 0.7 mgKOH / g or less and a hydroxyl value of 27 mgKOH / g or less, and even more preferably an acid value of 0.5 mgKOH / g or less and a hydroxyl value of 25 mgKOH / g or less. The acid value and hydroxyl value of the polyurethane resin may each be equal to or less than the measurement limit value by the measurement method described below. The polyurethane resin may have an acid value of 0.1 mgKOH / g or more. When the polyurethane resin has an acid value of 0.1 mgKOH / g or more, the carboxyl group in the polyurethane resin reacts with the isocyanate group in the isocyanate crosslinking agent, and the polyurethane resins can be bonded more strongly to each other. As a result, the solvent resistance of the film formed from the film-forming resin composition of the present disclosure is more likely to be improved. The polyurethane resin may have a hydroxyl value of 0.1 mgKOH / g or more. When the polyurethane resin has a hydroxyl value of 0.1 mgKOH / g or more, the hydroxyl group in the polyurethane resin reacts with the isocyanate group in the isocyanate crosslinking agent, and the polyurethane resins can be bonded more strongly to each other. As a result, the solvent resistance of the film formed from the film-forming resin composition of the present disclosure is more likely to be improved. The polyurethane resin may have an acid value of 0.1 mgKOH / g to 1.0 mgKOH / g and a hydroxyl value of 0.1 mgKOH / g to 30 mgKOH / g. When two or more polyurethane resins are used in combination, the acid value and hydroxyl value of the polyurethane resins as a whole may be within the above ranges.

[0014] In the present disclosure, the acid value of a polyurethane resin refers to a value measured by a method in accordance with JIS K0070:1992.

[0015] In the present disclosure, the hydroxyl value of a polyurethane resin refers to a value measured by a method in accordance with JIS K0070:1992.

[0016] When the amount of unreacted isocyanate groups in the polyurethane resin is low, the proportion of urethane bonds among the reactive groups in the polyurethane resin is relatively high, so that the urethane bonds and the isocyanate groups of the isocyanate crosslinking agent react to form allophanate bonds. Also, when the amount of unreacted isocyanate groups in the polyurethane resin is low, more isocyanate crosslinking agent that does not react with the polyurethane resin remains, so that isocyanate multimers and urea are easily formed. This makes it easier to form the pseudo-IPN structure described above, so that the solvent resistance and low-temperature impact resistance of the film formed from the film-forming resin composition of the present disclosure tend to be further improved. From this viewpoint, the amount of unreacted isocyanate groups in the polyurethane resin is preferably 2.0% by mass or less, more preferably 1.7% by mass or less, and even more preferably 1.5% by mass or less. In one embodiment, the amount of unreacted isocyanate groups in the polyurethane resin may be equal to or less than the measurement limit value by the measurement method described below. In another embodiment, the amount of unreacted isocyanate groups in the polyurethane resin may be 0.1% by mass or more.

[0017] In the present disclosure, the amount of unreacted isocyanate groups in a polyurethane resin refers to a value measured by a method conforming to Method A of JIS K1603-1:2007.

[0018] The elongation of the polyurethane resin at 23° C. is preferably 50% GL to 1000% GL, more preferably 75% GL to 750% GL, and even more preferably 100% GL to 500% GL, from the viewpoint of preventing cracking of the film when the film formed from the film-forming resin composition of the present disclosure is three-dimensionally molded. When two or more polyurethane resins are used in combination, the elongation of the mixture of polyurethane resins at 23° C. is preferably in the above range. Furthermore, when two or more types of polyurethane-based resins are used in combination, the polyurethane-based resin preferably includes a first polyurethane-based resin having an elongation at 23°C of 50% GL to 1000% GL and a second polyurethane-based resin having an elongation at 23°C of 50% GL to 1000% GL, more preferably a first polyurethane-based resin having an elongation at 23°C of 100% GL to 200% GL and a second polyurethane-based resin having an elongation at 23°C of 200% GL to 400% GL, and even more preferably a first polyurethane-based resin having an elongation at 23°C of 120% GL to 180% GL and a second polyurethane-based resin having an elongation at 23°C of 250% GL to 350% GL.

[0019] The yield point of the polyurethane resin at 23° C. is preferably 0.5 N to 20 N, more preferably 1.0 N to 15 N, and even more preferably 1.5 N to 10 N, from the viewpoint of preventing cracking of the film when the film formed from the film-forming resin composition of the present disclosure is three-dimensionally molded. When two or more polyurethane resins are used in combination, the yield point at 23° C. of the mixture of polyurethane resins is preferably in the above range. Furthermore, when two or more polyurethane-based resins are used in combination, it is preferable that the polyurethane resin comprises a first polyurethane-based resin having a yield point of 0.5 N to 20 N at 23°C and a second polyurethane-based resin having a yield point of 0.5 N to 20 N at 23°C, it is more preferable that the polyurethane resin comprises a first polyurethane-based resin having a yield point of 0.5 N to 5.0 N at 23°C and a second polyurethane-based resin having a yield point of 5.0 N to 20 N at 23°C, and it is even more preferable that the polyurethane resin comprises a first polyurethane-based resin having a yield point of 1.5 N to 3.0 N at 23°C and a second polyurethane-based resin having a yield point of 7.0 N to 10 N at 23°C.

[0020] The Young's modulus of the polyurethane resin at 23° C. is preferably 10 MPa to 2000 MPa, more preferably 20 MPa to 1500 MPa, and even more preferably 30 MPa to 1000 MPa, from the viewpoint of preventing cracking of the film when the film formed from the film-forming resin composition of the present disclosure is three-dimensionally molded. When two or more polyurethane resins are used in combination, the Young's modulus of the mixture of polyurethane resins at 23° C. is preferably within the above range. In addition, when two or more polyurethane-based resins are used in combination, it is preferable that the polyurethane-based resin comprises a first polyurethane-based resin having a Young's modulus at 23°C of 10 MPa to 2000 MPa and a second polyurethane-based resin having a Young's modulus at 23°C of 10 MPa to 2000 MPa, it is more preferable that the polyurethane-based resin comprises a first polyurethane-based resin having a Young's modulus at 23°C of 20 MPa to 200 MPa and a second polyurethane-based resin having a Young's modulus at 23°C of 200 MPa to 1500 MPa, and it is even more preferable that the polyurethane-based resin comprises a first polyurethane-based resin having a Young's modulus at 23°C of 30 MPa to 100 MPa and a second polyurethane-based resin having a Young's modulus at 23°C of 300 MPa to 500 MPa.

[0021] In the present disclosure, the elongation, yield point and Young's modulus at 23°C of a polyurethane-based resin refer to values ​​determined by conducting a tensile test on a test piece having an average thickness of 35 μm, a length of 150 mm and a width of 10 mm using a tensile tester with a gripping distance of 100 mm and a tensile speed of 300 mm / min.

[0022] The polyurethane-based resin preferably includes at least one selected from the group consisting of polycarbonate-based polyurethane resins, polyester-based polyurethane resins, and polyether-based polyurethane resins, and from the viewpoint of improving the weather resistance of the film formed from the film-forming resin composition of the present disclosure, a polycarbonate-based polyurethane resin is more preferred.

[0023] The proportion of polyurethane resin in the solid content of the film-forming resin composition is not particularly limited, and from the viewpoint of further improving the low-temperature impact resistance of the film formed from the film-forming resin composition of the present disclosure, it is preferably 50% by mass to 90.9% by mass, more preferably 60% by mass to 88.8% by mass, and even more preferably 80% by mass to 86.9% by mass.

[0024] As the polyurethane resin, commercially available products can be used. Examples of commercially available polyurethane resins include "NE-8836 (polycarbonate-based)", "NE-8811 (polycarbonate-based)", "NE-8850 (polycarbonate-based)" (manufactured by Dainichiseika Color & Chemicals Co., Ltd.), "Superflex 420 (polycarbonate-based)", "Superflex 460 (polycarbonate-based)", and "Superflex 210 (polyester-based)" (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), "Pandex T-9280 (polycarbonate-based)", "Pandex T-9290 (polycarbonate-based)", "Pandex T-1190 (polyester-based)", and "Pandex T-8190 (polyether-based)" (all manufactured by DIC Covestro Polymer Co., Ltd.).

[0025] (Isocyanate-based crosslinking agent) The film-forming resin composition of the present disclosure includes an isocyanate-based crosslinking agent. The type of the isocyanate-based crosslinking agent is not particularly limited, and any conventionally known isocyanate-based crosslinking agent can be used. The isocyanate-based crosslinking agent may be used alone or in combination of two or more types. In the present disclosure, the term "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in one molecule (so-called polyisocyanate compound).

[0026] Examples of the isocyanate crosslinking agent include aromatic polyisocyanate compounds such as xylylene diisocyanate (XDI), diphenylmethane diisocyanate, triphenylmethane triisocyanate, and tolylene diisocyanate (TDI), and aliphatic polyisocyanate compounds or alicyclic polyisocyanate compounds such as hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate, and hydrogenated aromatic polyisocyanate compounds. Further, examples of the isocyanate-based crosslinking agent include dimers, trimers, and pentamers of the above polyisocyanate compounds, adducts of the above polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret forms of the above polyisocyanate compounds. From the viewpoint of easiness in forming a pseudo IPN structure, an aliphatic polyisocyanate compound is preferred, and a linear aliphatic polyisocyanate compound is more preferred.

[0027] As the isocyanate-based crosslinking agent, a commercially available product can be used. Examples of commercially available isocyanate crosslinking agents include "Coronate (registered trademark) HX", "Coronate (registered trademark) HL-S", "Coronate (registered trademark) L", "Coronate (registered trademark) L-45E", "Coronate (registered trademark) 2031", "Coronate (registered trademark) 2037", "Coronate (registered trademark) 2234", "Coronate (registered trademark) 2785", "Aquanate (registered trademark) 200", and "Aquanate (registered trademark) 210" (all manufactured by Tosoh Corporation), "Sumidur (registered trademark) N3300", "Desmodur (registered trademark) N3400", and "Sumidur (registered trademark) N75" (all manufactured by Sumika Covestro Urethane Co., Ltd.), "Duranate (registered trademark) E-405-80T", "Duranate (registered trademark) AE700-100", "Duranate (registered trademark) Examples of such compounds include "Takenate (registered trademark) D-110N", "Takenate (registered trademark) D-120N", "Takenate (registered trademark) M-631N", "MT-Olestar (registered trademark) NP1200", "STABIO (registered trademark) D-370N" and "STABIO (registered trademark) XD-340N" (all manufactured by Mitsui Chemicals, Inc.), and "Resamine X-100" (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.).

[0028] The content of the isocyanate-based crosslinking agent is 10 parts by mass to 30 parts by mass per 100 parts by mass of the polyurethane resin (100 parts by mass of the total polyurethane resin when two or more kinds of polyurethane resins are used in combination). If the content of the isocyanate-based crosslinking agent is 10 parts by mass or more per 100 parts by mass of the polyurethane resin, the solvent resistance of the film formed from the resin composition for film formation of the present disclosure can be further improved. If the content of the isocyanate-based crosslinking agent is 30 parts by mass or less per 100 parts by mass of the polyurethane resin, the low-temperature impact resistance of the film formed from the resin composition for film formation of the present disclosure can be further improved. The content of the isocyanate-based crosslinking agent is preferably 12.5 parts by mass to 27.5 parts by mass, more preferably 15 parts by mass to 25 parts by mass, per 100 parts by mass of the polyurethane resin.

[0029] (Cross-linking catalyst) The film-forming resin composition of the present disclosure includes a crosslinking catalyst. The crosslinking catalyst promotes a crosslinking reaction between a urethane bond in a polyurethane resin and an isocyanate group in an isocyanate crosslinking agent. In addition, when the polyurethane resin contains a hydroxyl group, a carboxyl group, or the like, the crosslinking catalyst also promotes a crosslinking reaction between the hydroxyl group, the carboxyl group, or the like and the isocyanate group in an isocyanate crosslinking agent. The type of the crosslinking catalyst is not particularly limited, and any conventionally known crosslinking catalyst capable of promoting the crosslinking reaction between the urethane bond, hydroxyl group, carboxyl group, etc. in the polyurethane resin and the isocyanate group in the isocyanate crosslinking agent can be used. The crosslinking catalyst may be used alone or in combination of two or more kinds.

[0030] Examples of the crosslinking catalyst include metal crosslinking catalysts, amine crosslinking catalysts, etc. Among these, it is preferable to contain a metal crosslinking catalyst from the viewpoints of obtaining a high catalytic effect with a small amount and further improving the transparency of the obtained film. In the present disclosure, the term "metallic cross-linking catalyst" refers to a cross-linking catalyst that contains a metal atom in the molecule. When the crosslinking catalyst is a combination of a metal crosslinking catalyst and another crosslinking catalyst, the ratio of the metal crosslinking catalyst in the crosslinking catalyst is preferably 50% by mass or more, more preferably 75% by mass or more, and even more preferably 95% by mass or more. The ratio of the metal crosslinking catalyst in the crosslinking catalyst may be 100% by mass.

[0031] Examples of the metal cross-linking catalyst include an organotin cross-linking catalyst, an organolead cross-linking catalyst, an organozinc cross-linking catalyst, a metal chelate catalyst, etc. Among these, an organotin cross-linking catalyst is preferred. Specific examples of the metal cross-linking catalyst include tin 2-ethylhexanoate, di-n-octyltin dilaurate, dibutyltin diacetate, dibutyltin dilaurate, dibutyltin oxide, dibutyltin dichloride, etc. Among these, at least one of tin 2-ethylhexanoate and di-n-octyltin dilaurate is preferred, and at least tin 2-ethylhexanoate is more preferred. When an organic tin crosslinking catalyst is used in combination with another crosslinking catalyst as a crosslinking catalyst, the proportion of the organic tin crosslinking catalyst in the crosslinking catalyst is preferably 50% by mass or more, more preferably 75% by mass or more, and even more preferably 95% by mass or more. The proportion of the organic tin crosslinking catalyst in the crosslinking catalyst may be 100% by mass.

[0032] The content of the crosslinking catalyst is 0.01 parts by mass or more per 100 parts by mass of the polyurethane resin (100 parts by mass of the polyurethane resins in total when two or more kinds of polyurethane resins are used in combination). If the content of the crosslinking catalyst is 0.01 parts by mass or more per 100 parts by mass of the polyurethane resin, the solvent resistance of the film formed from the film-forming resin composition of the present disclosure can be further improved. The content of the crosslinking catalyst is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more per 100 parts by mass of the polyurethane resin. The content of the crosslinking catalyst may be 10 parts by mass or less, or 5 parts by mass or less, per 100 parts by mass of the polyurethane resin, from the viewpoint of suppressing the occurrence of cloudiness in the film-forming resin composition. The content of the crosslinking catalyst is preferably 0.01 to 10 parts by mass with respect to 100 parts by mass of the polyurethane resin.

[0033] (Organic solvent) The film-forming resin composition of the present disclosure may contain an organic solvent from the viewpoint of obtaining a smooth coating appearance. The type of organic solvent is not particularly limited, and is not particularly limited as long as it dissolves or disperses various components contained in the film-forming resin composition. Examples of the organic solvent include ketone-based organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester-based organic solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; aliphatic hydrocarbon-based organic solvents such as n-hexane, n-heptane, and n-octane; alicyclic hydrocarbon-based organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, and cyclooctane; aromatic hydrocarbon-based organic solvents such as toluene and xylene; and amide-based organic solvents such as N,N-dimethylformamide. The organic solvents may be used alone or in combination of two or more. The content of the organic solvent is appropriately set in consideration of the coating method of the film-forming resin composition of the present disclosure, drying conditions, types of components contained in the composition, and the like.

[0034] (Other Ingredients) The film-forming resin composition of the present disclosure may contain other components such as a solvent, a plasticizer, a softener, a dye, a pigment, an inorganic filler, an ultraviolet absorber, a light stabilizer, an antioxidant, an antifoaming agent, and a surfactant, as necessary. When the resin composition for forming a film of the present disclosure contains other components, the content thereof is not particularly limited and may be appropriately set within a range that does not affect the effects of the resin composition for forming a film of the present disclosure.

[0035] <Overlaminate film> The overlaminate film of the present disclosure comprises a surface protective film formed from the film-forming resin composition of the present disclosure, and a pressure-sensitive adhesive layer provided on one side of the surface protective film. The overlaminate film of the present disclosure has a surface protective film formed from the film-forming resin composition of the present disclosure, and therefore has excellent solvent resistance and low-temperature impact resistance.

[0036] The method for forming a surface protective film using the film-forming resin composition of the present disclosure is not particularly limited. For example, the surface protective film can be formed by a known method using a single-layer T-die extruder, a multi-layer T-die extruder, a calendar molding machine, etc. In addition, a surface protective film can be formed by applying the film-forming resin composition of the present disclosure containing an organic solvent to one side of a release-treated temporary support such as a polyethylene terephthalate film, a polypropylene film, or paper, and drying it. Examples of such application methods include screen printing, gravure printing, bar coating, knife coating, roll coating, comma coating, blade coating, die coating, spray painting, and methods using an applicator. The crosslinking reaction may be promoted by heating the surface protection film. Examples of a method for heating the surface protection film include drying with hot air and heating with a heating device such as an oven or a hot plate.

[0037] The average thickness of the surface protective film is appropriately set depending on the application of the overlaminate film. The average thickness of the surface protective film may be, for example, 20 μm to 100 μm.

[0038] From the viewpoint of achieving both solvent resistance and low-temperature impact resistance of the surface protection film, the gel fraction of the surface protection film is preferably 20% by mass to 60% by mass, more preferably 35% by mass to 50% by mass, and even more preferably 40% by mass to 50% by mass. In the present disclosure, the gel fraction refers to a value determined by the method described in the Examples.

[0039] The adhesive layer constituting the overlaminate film is not particularly limited in terms of its components as long as it can adhere to an adherend such as a resin plate, a metal plate, a glass plate, etc., and can be formed using a (meth)acrylic adhesive, a silicone adhesive, a synthetic rubber adhesive, etc. Among these, from the viewpoint of further improving adhesion to the adherend and durability, it is preferable to form it using a (meth)acrylic adhesive. There are no particular restrictions on the average thickness of the pressure-sensitive adhesive layer, but from the viewpoint of further improving the adhesion to the adherend, it is preferably in the range of 5 μm to 100 μm. The pressure-sensitive adhesive layer may contain various additives to the extent that the adhesiveness is not impaired. Examples of such additives include crosslinking agents, crosslinking catalysts, dispersants, ultraviolet absorbers, light stabilizers, heat stabilizers, plasticizers, tackifiers, fillers, colorants, etc.

[0040] Fig. 1 is a cross-sectional view of one embodiment of the overlaminate film of the present disclosure. The overlaminate film 10 in Fig. 1 includes a surface protective film 20 and a pressure-sensitive adhesive layer 30 provided on one side of the surface protective film 20. Details of the surface protective film 20 and the pressure-sensitive adhesive layer 30 are as described above.

[0041] The overlaminate film may have layers other than the surface protective film and the pressure-sensitive adhesive layer, if necessary. The other layers include a decorative layer provided on the surface protective film and / or between the surface protective film and the adhesive layer. The decorative layer is a layer provided to impart design to the overlaminate film, and is a pattern layer that expresses patterns, letters, patterned pictures, etc. The decorative layer can be formed by a known printing method such as inkjet printing, screen printing, gravure printing, hot stamp printing, and baking printing. Furthermore, examples of layers other than the decorative layer include an easy-adhesion layer provided between the surface protection film and the pressure-sensitive adhesive layer.

[0042] The overlaminate film of the present disclosure can be used as a constituent member of the license plate of the present disclosure described below. In addition to license plates, the overlaminate film of the present disclosure can be used for the interior or exterior of vehicles such as automobiles, and for interior applications of buildings such as walls, floors, and ceilings.

[0043] <License plate> The license plate of the present disclosure comprises a plate substrate and an overlaminate film of the present disclosure provided on one side of the plate substrate. The configuration of the license plate of the present disclosure is not particularly limited, but it is preferable that a surface protection film formed from the film-forming resin composition of the present disclosure, which has excellent solvent resistance and low-temperature impact resistance, constitutes the outermost layer of the license plate. In the case where the surface protection film formed by the film-forming resin composition of the present disclosure constitutes the outermost layer of the license plate, characters may be formed on the outermost surface of the surface protection film as a decorative layer. The characters formed on the outermost surface of the surface protection film are preferably formed by baking printing. Hereinafter, in the license plate of the present disclosure, the "adhesive layer" provided on the overlaminate film of the present disclosure will also be referred to as the "first adhesive layer." The number plate of the present disclosure may have, for example, a configuration in which the adhesive layer (so-called first adhesive layer) side of the overlaminate film of the present disclosure is attached to one side of the plate substrate, or may have an image receiving layer capable of forming a printed image on the surface between the plate substrate and the overlaminate film of the present disclosure. The image receiving layer may constitute an image receiving film together with a second adhesive layer that allows the image receiving layer to be adhered to the plate substrate. In this case, from the viewpoint of imparting low-temperature impact resistance and printability to the image receiving layer, it is preferable that the image receiving layer contains a polyurethane resin, a (meth)acrylic resin, and a white pigment. In addition, from the viewpoint of further improving weather resistance, durability, and adhesion to the plate substrate, it is preferable that the second adhesive layer contains a (meth)acrylic resin. In addition, it is preferable that the second adhesive layer further contains a pigment from the viewpoint of improving the appearance of the number plate. When the license plate of the present disclosure has an image receiving layer, a printed image may be provided on the image receiving layer as a decorative layer. As a method for forming a printed image on the image receiving layer, known printing methods such as inkjet printing, screen printing, and gravure printing can be applied.

[0044] Fig. 2 is a cross-sectional view of one embodiment of the license plate of the present disclosure. The license plate 40 of Fig. 2 comprises a plate substrate 50 and an overlaminate film 10 of the present disclosure provided on one side of the plate substrate 50. The adhesive layer (first adhesive layer) 30 side of the overlaminate film 10 is in contact with one side of the plate substrate 50. In the license plate 40, a decorative layer 60 is provided on the surface protection film 20 of the overlaminate film 10. 3 is a cross-sectional view of another embodiment of the license plate of the present disclosure. The license plate 70 of FIG. 3 includes a plate substrate 50, an image receiving film 100 having an image receiving layer 80 and a second adhesive layer 90, and an overlaminate film 10 of the present disclosure. The second adhesive layer 90 side of the image receiving film 100 is in contact with one side of the plate substrate 50. The adhesive layer (first adhesive layer) 30 side of the overlaminate film 10 is in contact with the image receiving layer 80 of the image receiving film 100. In the license plate 70, a decorative layer 60 is provided on the surface protective film 20 of the overlaminate film 10. In addition, in the license plate 70, the decorative layer 60 is formed on the image receiving layer 80 of the image receiving film 100. The details of the plate substrate 50 will be described later. The details of the overlaminate film 10, the decorative layer 60 and the image receiving film 100 are as described above.

[0045] As the plate substrate, a metal plate or a resin plate can be used. Examples of the metal plate include an aluminum plate, a stainless steel plate, and an iron plate. Examples of the resin plate include a polycarbonate plate, a polyester plate, a polyvinyl chloride plate, an acrylic plate, an ABS plate, and a PP plate. If necessary, these plate materials may be molded into a shape such as a frame. EXAMPLES

[0046] The present disclosure will be described in more detail below based on examples, but the present disclosure is not limited to these examples.

[0047] <Preparation of film-forming resin composition and production of film> Polyurethane resin 1, polyurethane resin 2, isocyanate crosslinking agent, and crosslinking catalyst in the amounts shown in Table 1, and N,N-dimethylformamide as a dilution solvent were mixed and stirred using a disper at 23° C. for 10 minutes to prepare the film-forming resin compositions of Examples 1 to 14 and Comparative Examples 1 to 4. The dilution solvent was mixed in an amount of 13 parts by mass per 100 parts by mass of the total of the polyurethane resins. Next, the film-forming resin composition was applied using an applicator to a polyethylene terephthalate film (manufactured by Lintec Corporation, thickness: 75 μm, product name P756050) that had been subjected to a release treatment so that the average thickness after drying would be as shown in Table 1, and the film was dried by heating in an atmosphere of 100°C for 3 minutes and in an atmosphere of 160°C for 3 minutes to produce the films of Examples 1-14 and Comparative Examples 1-4. In Table 1, the details of each component contained in the film-forming resin composition are as follows. NE-8836: One-component non-yellowing polycarbonate-based urethane resin [manufactured by Dainichiseika Chemicals Mfg. Co., Ltd.], acid value: 0.3 mg KOH / g, hydroxyl value: 15 mg KOH / g, amount of unreacted isocyanate groups: 0.3 mass%, elongation at 23°C: 166% GL, yield point: 8.7 N, Young's modulus: 431.7 MPa NE-8811: One-component non-yellowing polycarbonate-based urethane resin [manufactured by Dainichiseika Chemicals Mfg. Co., Ltd.], acid value: 0.3 mg KOH / g, hydroxyl value: 17 mg KOH / g, amount of unreacted isocyanate groups: 1.2 mass%, elongation at 23°C: 278% GL, yield point: 1.7 N, Young's modulus: 65.0 MPa Resamine X-100: Isocyanate-based crosslinking agent (manufactured by Dainichiseika Color & Chemicals Co., Ltd.) Sumidur N3300: Hexamethylene diisocyanate trimer (manufactured by Sumika Covestro Urethane Co., Ltd.) STABIO D-370N: Pentamethylene diisocyanate polyisocyanate [Mitsui Chemicals, Inc.] · UA-38: 2-ethylhexanoate (Tokushiki Co., Ltd.) OT-1: Di-n-octyltin dilaurate (made by ADEKA Corporation)

[0048] In Comparative Example 5, a vinyl chloride film "08C040M" (manufactured by Nippon Carbide Industries Co., Ltd.) was prepared. In Comparative Example 6, an acrylic film "HBD002" (manufactured by Mitsubishi Chemical Corporation) was prepared. In Comparative Example 7, a fluorine-based film "14S0250" (manufactured by Denka Co., Ltd.) was prepared.

[0049] The elongation, yield point and Young's modulus at 23° C. for each polyurethane resin (NE-8836 and NE-8811) were measured as follows. Each polyurethane resin and N,N-dimethylformamide as a dilution solvent were mixed and stirred for 10 minutes at 23°C using a disper, and the obtained solution was applied to an untreated polyethylene terephthalate film (manufactured by Lintec Corporation, thickness: 75μm, P756050 (product name)) using an applicator so as to have an average thickness of 35μm, and the film was formed by heating and drying for 3 minutes at 100°C and then for 3 minutes at 160°C. The amount of the dilution solvent was 13 parts by mass per 100 parts by mass of the total polyurethane resins. The film thus obtained was cut into a length of 150 mm and a width of 10 mm, and a tensile test was carried out using a tensile tester (manufactured by A&D Co., Ltd., product name RTG-1310) at a gripping distance of 100 mm and a tensile speed of 300 mm / min to determine the elongation, yield point, and Young's modulus. The measurement temperature was 23°C.

[0050] [Solvent resistance evaluation] The gel fraction of each of the films produced or prepared was measured, and the solvent resistance of each film was evaluated based on the gel fraction value. The "gel fraction of a film" refers to the proportion of solvent-insoluble matter measured using a 1:1 (by mass) mixture of toluene and isopropyl alcohol as an extraction solvent. Specifically, the gel fraction of the film was measured according to the following (1) to (4). (1) About 0.15 g of film was attached to a 250 mesh wire net (100 mm x 100 mm) whose mass was accurately measured using a precision balance, and the wire net was folded five times with the attached film on the inside to prevent leakage of the gel, to prepare a sample. The mass was then accurately measured using a precision balance. (2) The obtained sample was immersed in 80 mL of a solvent prepared by mixing toluene and isopropyl alcohol in a 1:1 ratio (by mass) at 23°C for 3 days. (3) The sample was taken out, washed with a small amount of the mixed solvent, and dried for 24 hours at 120° C. Then, the mass was accurately measured using a precision balance. (4) The gel fraction was calculated using the following formula. Gel fraction (unit: mass%) = (ZX) / (YX) x 100 where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the film attached before immersion (unit: g), and Z is the mass of the wire mesh with the film attached after immersion and drying (unit: g). The evaluation criteria were as follows: "A" and "B" are practically acceptable levels, with "A" being the most preferable. The results are shown in Table 1. A: 40% by mass or more B: 20% by mass or more and less than 40% by mass C: Less than 20% by mass

[0051] [Low temperature impact resistance evaluation] (1) Preparation of (meth)acrylic copolymer A A reactor equipped with a stirrer, a reflux condenser, a successive dropping device, and a thermometer was charged with 25 mass% of a monomer mixture consisting of 49.0 parts by mass of n-butyl acrylate, 50.0 parts by mass of methyl acrylate, and 1.0 part by mass of acrylic acid, 45.0 parts by mass of ethyl acetate [organic solvent], and 0.015 parts by mass of 2,2'-azobisisobutyronitrile [AIBN; polymerization initiator], and the mixture was heated to carry out polymerization at the reflux temperature for 20 minutes. Next, the remaining 75% by mass of the monomer mixture and a polymerization initiator solution consisting of 30.0 parts by mass of ethyl acetate and 0.15 parts by mass of 2,2'-azobisisobutyronitrile were successively dropped into the polymerization reaction product in the reactor maintained at reflux temperature over 1.5 hours, and the polymerization reaction was continued for 1 hour, and then a polymerization initiator solution consisting of 25.0 parts by mass of ethyl acetate and 0.30 parts by mass of 2,2'-azobisisobutyronitrile was successively dropped into the polymerization reaction product in 1 hour, and the polymerization reaction was continued for another 2 hours to obtain a polymerization reaction product. The obtained polymerization reaction product was diluted to a solid content concentration of 35% by mass using methyl ethyl ketone (MEK), and then cooled to obtain a solution of (meth)acrylic copolymer A. The "solid content concentration" here means the mass ratio of (meth)acrylic copolymer A in the solution of (meth)acrylic copolymer A. (2) Preparation of (meth)acrylic copolymer B A reactor equipped with a stirrer, a reflux condenser, a successive dropping device, and a thermometer was charged with 20 mass% of a monomer mixture consisting of 80.0 parts by mass of methyl methacrylate, 14.0 parts by mass of ethyl acrylate, and 6.0 parts by mass of 2-dimethylaminoethyl methacrylate, 45.0 parts by mass of ethyl acetate [organic solvent], and 0.15 parts by mass of 2,2'-azobisisobutyronitrile [AIBN; polymerization initiator], and the mixture was heated to carry out polymerization at the reflux temperature for 20 minutes. The remaining 80% by mass of the monomer mixture and a polymerization initiator solution consisting of 30.0 parts by mass of ethyl acetate and 0.15 parts by mass of 2,2'-azobisisobutyronitrile were successively dropped into the polymerization reaction product in the reactor maintained at reflux temperature over 1.5 hours, and the reaction was maintained for 1 hour to polymerize, and then a polymerization initiator solution consisting of 25.0 parts by mass of ethyl acetate and 0.30 parts by mass of 2,2'-azobisisobutyronitrile was successively dropped into the polymerization reaction product over 1 hour, and the polymerization reaction was continued for another 2 hours to obtain a polymerization reaction product. The obtained polymerization reaction product was diluted to a solid content concentration of 36% by mass using methyl ethyl ketone (MEK), and then cooled to obtain a solution of (meth)acrylic copolymer B. The "solid content concentration" here means the mass ratio of (meth)acrylic copolymer B in the solution of (meth)acrylic copolymer B. (3) Preparation of adhesive layer A pressure-sensitive adhesive composition was obtained by mixing and stirring 100 parts by mass (solid content equivalent) of a solution of (meth)acrylic copolymer A, 15 parts by mass (solid content equivalent) of a solution of (meth)acrylic copolymer B, and 0.05 parts by mass (solid content equivalent) of an epoxy-based crosslinking agent (TETRAD-C, manufactured by Mitsubishi Gas Chemical Company, Inc.) as a crosslinking agent. The obtained adhesive composition was applied to a release-treated polyethylene terephthalate film (manufactured by Lintec Corporation, thickness: 75 μm, PET75GS (product name)) so that the average thickness after drying would be 25 μm, and the film was heated and dried for 1 minute in a 100°C atmosphere, and then laminated to a film that had been produced or prepared to produce an adhesive-attached sheet (overlaminate film). The release-treated polyethylene terephthalate film was removed from the adhesive-attached sheet, and the sheet was laminated to an aluminum plate in a 23°C, 50% RH environment, and heat-treated at 120°C for 1 hour to produce a test piece. The prepared test pieces were subjected to an evaluation test for impact resistance in a low-temperature chamber (product name: constant temperature and humidity chamber, built-in chamber E series, manufactured by Espec Corp.) with the ambient temperature set to -30°C. Specifically, in the low-temperature chamber, the test pieces were subjected to an impact test under the following conditions using a DuPont impact tester (product name: DuPont impact tester, manufactured by TP Giken Corp.) in accordance with the method of JIS K 5600-5-3:1999. The obtained results are shown in Table 1. Weight: 500g Die tip radius: 6.35mm The evaluation criteria were as follows: "A" and "B" are practically acceptable levels, with "A" being the most preferable. A: The film does not crack when tested from a drop height of 100 cm. B: The film does not crack when tested from a drop height of 50 cm, but cracks occur when tested from a drop height of 100 cm. C: The film cracks when tested from a drop height of 50 cm.

[0052] [Table 1]

[0053] The film of Comparative Example 1, which did not contain either an isocyanate-based crosslinking agent or a crosslinking catalyst, was poor in solvent resistance. The film of Comparative Example 2, in which the content of the isocyanate-based crosslinking agent was less than 10 parts by mass relative to 100 parts by mass of the polyurethane-based resin, was poor in solvent resistance. The film of Comparative Example 3, in which the content of the isocyanate-based crosslinking agent exceeded 30 parts by mass relative to 100 parts by mass of the polyurethane-based resin, was poor in low-temperature impact resistance. The film of Comparative Example 4, in which no crosslinking catalyst was used, was poor in solvent resistance. The vinyl chloride film used in Comparative Example 5 was poor in low-temperature impact resistance. The acrylic film used in Comparative Example 6 was poor in solvent resistance and low-temperature impact resistance. The fluorine-based film used in Comparative Example 7 was poor in low-temperature impact resistance. On the other hand, the films of the Examples were superior in solvent resistance and low-temperature impact resistance to the films of the Comparative Examples, and were capable of achieving both of these properties. [Explanation of symbols]

[0054] 10 Overlamination film 20 Surface protection film 30 Adhesive layer (first adhesive layer) 40, 70 license plate 50 Plate substrate 60 Decorative Layer 80 Image Receptive Layer 90 Second adhesive layer 100 Image Receptive Film

Claims

1. The composition includes a polyurethane resin, an isocyanate crosslinking agent, and a crosslinking catalyst, The film-forming resin composition comprises, relative to 100 parts by mass of the polyurethane resin, a content of the isocyanate-based crosslinking agent of 10 parts by mass to 30 parts by mass and a content of the crosslinking catalyst of 0.01 parts by mass or more.

2. 2. The film-forming resin composition according to claim 1, wherein the polyurethane-based resin comprises at least one selected from the group consisting of polycarbonate-based polyurethane resins, polyester-based polyurethane resins, and polyether-based polyurethane resins.

3. 2. The film-forming resin composition according to claim 1, wherein the polyurethane resin has an acid value of 1.0 mgKOH / g or less and a hydroxyl value of 30 mgKOH / g or less.

4. The film-forming resin composition according to claim 1 , wherein the crosslinking catalyst comprises a metal crosslinking catalyst.

5. 5. The film-forming resin composition according to claim 4, wherein the metal crosslinking catalyst is at least one of tin 2-ethylhexanoate and di-n-octyltin dilaurate.

6. An overlaminate film comprising a surface protective film formed from the film-forming resin composition according to any one of claims 1 to 5, and a pressure-sensitive adhesive layer provided on one side of the surface protective film.

7. The overlaminate film according to claim 6, wherein the surface protective film has a gel fraction of 20% by mass to 60% by mass.

8. A license plate comprising a plate substrate and the overlaminate film of claim 6 provided on one surface side of the plate substrate.

9. 9. The license plate of claim 8, further comprising an image receiving layer between the plate substrate and the overlaminate film.

Citation Information

Patent Citations

  • Adhesive composition for protection films, and protection film

    JP2017155099A

  • Ultraviolet absorber-resistant polyurethane composition, and coating material prepared with the composition

    JP2018021151A

  • Polyurethane resin film and method for producing the same

    JP2018039169A

  • Curable resin composition and laminate

    JP2019194295A

  • Graphic film for licence plate, graphic film laminated plate, licence plate and method of manufacturing the same

    JP2019206145A